Kids edutainment application: islamic pre-school syllabus (KEAIPS) - Anis Izzati, Ab Fauzan (2015)
Pre-schoolers as defined in Malaysia’s environment are kids in range of 4 to 6 years old who go for a formal education in either government or private kindergarten. Humans at this period are still in their pure state with high inquisitiveness that will absorb new knowledge easily, especially when it comes to spiritual education, specifically to Islamic teachings. The wrecking youth nowadays are most probably due to lack of understanding to the fundamentals of Islamic teachings. In order to peg the awareness of Islamic teaching’s in a human’s life, a platform which act as the introducer to the awareness is highly recommended to be develop. Kids Edutainment Application: Islamic Pre-School Syllabus (KEAIPS) is here to aid this needs